PENGARUH WAITING TIME SATISFACTION DAN SERVICE SATISFACTION TERHADAP LOYALITAS KONSUMEN NOKIA CARE di WTC MALL - Julindrastuti, Dijah (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2011)
Waiting is the work of the boring, throw julian, dam Creating Comfortable feeling is not regular. World Kesawan Marketing services in particular, there's always time waitng ON The shipping process. Benefits Service is any activity or the One offered Created shareholders party to the essentially intangible regular and regular APA does not produce any ownership. From the description on the top, then Author Title interested in taking RESEARCH